Effect of UV-A radiation on photosynthetic electron transport - Turcsányi, Enikő; Vass, Imre (Acta Biologica Szegediensis, 2002)
We have studied the inhibition of photosynthetic electron transport by UV-A (320-400nm) radiation in isolated spinach thylakoids by flash-induced oxygen and thermoluminescence (TL) measurements. The flash pattern of oxygen evolution showed an increased amount of the S0 state in the dark, which indicate a direct effect of UV-A radiation in the water-oxidizing complex. TL measurements revealed the UV-A induced loss of PSII centers. Flash-induced oscillation of the B TL band, originating from the S2Q8 recombination, indicated a UV-A induced decrease in the amount of Q8 relative to Q8. In conclusion, our data show that UV-A radiation is highly damaging for PSII, whose electron transport is affected both at the water oxidizing complex, and the binding site of the Q8 quinone electron acceptor.